Dissolution and electrolysis of lunar regolith in ionic liquids. (15th September 2022) - Rohde, Sebastian; Wiltsche, Helmar; Cowley, Aidan; Gollas, Bernhard
Abstract: Oxygen extraction from lunar regolith is one of the key in-situ resource utilization methods required for a permanent human presence on the moon. In this work an electrolysis-based extraction method was investigated, which works with innocuous chemicals and at moderate temperatures. EAC-1 was utilized as lunar regolith simulant and the ionic liquid 1-ethyl-3-methylimidazolium hydrogen sulfate was used as electrolyte. The working principle of this method, which was pioneered by Paley et al.2009, is envisaged as a three step process. First, water is generated by the dissolution of regolith in the Brønsted acidic ionic liquid. This water is electrolyzed, yielding oxygen and hydrogen as an intermediate product. Finally, the ionic liquid is regenerated by anodic oxidation of hydrogen and cathodic reduction of the dissolved metal ions. A gravimetric investigation showed that approximately 30 ​wt% of EAC-1 can be solubilized, if at least 6 ​g of ionic liquid are used per gram of EAC-1. Phosphorous oxide was found to be the most soluble compound with 82.0 ± 3.1% of the total amount in solution, followed by MgO, Na2 O, K2 O, Al2 O3, iron oxides, TiO2 and CaO in decreasing order as determined by inductively coupled plasma optical emission spectrometry (ICP-OES). Cyclic voltammetry of the neat ionic liquid revealed that reduction of H + is the dominant cathodic reaction of the electrolyte. The cyclic voltammogram of the EAC-1 solution showed a Fe 2+ /Fe 3+ redox peak pair, yet no distinct current, which could be attributed to further reduction of metal ions and electrodeposition. An investigation of the electrode surfaces with SEM and EDX after potential controlled electrolysis experiments at strongly negative cathodic potentials did not reveal any signs of metal deposition and ionic liquid regeneration. Hence, more work is required to enable the ionic liquid regeneration of this oxygen extraction method by either inhibiting the hydrogen evolution reaction in the ionic liquid electrolyte or facilitating metal deposition. Highlights: Investigation of an oxygen extraction method from lunar regolith with electrolysis. Ionic liquid 1-ethyl-3-methylimidazolium hydrogen sulfate is used as electrolyte. Approximately 30 ​wt% of the lunar regolith simulant EAC-1 can be solubilized. ICP-OES analysis revealed P, Mg, Na, K, Al, Fe, Ti and Ca ions in solution. Hydrogen evolution reaction limits cathodic stability of the ionic liquid.